ChemInform Abstract: Ferrocene‐Based Supramolecular Structures and Their Applications in Electrochemical Responsive Systems. Issue 51 (23rd December 2014) - Peng, Liao; Feng, Anchao; Huo, Meng; Yuan, Jinying
Abstract Review: 92 refs.